Energy Transmission via Coupled Coils - Howard, Roy; Howard, Ian (Curtin University of Technology, Sarawak Campus, Malaysia, 2008)
The modelling of a N stage cascade of coupled coils is detailed for the general homogenous case and the specific non-homogenous case associated with energy coupling in joined pipe structures. Consistent with the practical situation, models are developed assuming the coils have different radii and have a lateral offset. A resonant structure, which facilitates energy transmission, is proposed. It is shown that the ability to transfer energy is relatively insensitive to frequency, within a few percent of the resonant frequency, to component tolerance and to load resistance. However, it is shown to be critically dependent on the level of mutual coupling between the two coils. It is practical for energy transmission, at greater than a 10mW level, over 8 stages consistent with a distance of 80m.